Highly efficient oil–water separators based on dual superhydrophobic and superoleophilic properties of multiwall-carbon nanotube filtration films. Issue 15 (29th January 2016) - Huang, Tsao-Cheng; Li, Peng; Yao, Haiqing; Sue, Hung-Jue; Kotaki, Masaya; Tsai, Mei-Hui
Abstract : A new alkyl-pyrene has been synthesized and is used to modify multiwall-carbon nanotube to form films. Our results reveal that the modified MWCNT film prepared here is a promising candidate for use in removal of oils from water. Abstract : A new alkyl-pyrene has been synthesized and is used to modify multiwall-carbon nanotube to form films that are both superhydrophobic and superoleophilic. The superhydrophobic property of the MWCNT films prevents water from going through and the superoleophilic property of the films attracts oil, facilitating it to pass through the MWCNT filtration films. This film can also be easily recycled to prepare brand new water–oil separation filters and can be easily scaled up for large sizes. Our results reveal that the modified MWCNT film prepared here is a promising candidate for use in removal of oils and other organic pollutants from water.